The Exploration of Radio Frequency Identification (RFID) Application in the Retail Industry: Based on Wal-Mart, Tesco and Sainsburys Case Studies Analysis - Gao, Yucheng (2010)
The purpose of this research is to show how radio frequency identification (RFID) benefits supply chain management and explore what difficulties will face by using this technology. It is based on the analysis of three real companies (Wal-Mart, Tesco and Sainsburys) to track how real organizations deploy RFID technology in their company, what problems they face and how operators plan strategies to overcome these difficulties. Furthermore, this research also indicates recommendations and solutions in order to help operators of the organization to better administer RFID in supply chain management. This study utilizes qualitative methodology through the collection of journals, books and company records to explain the impact of RFID on performances. A wide range of literature review which includes the working principles, history review, advantages, obstacles, and applications will be described. Meanwhile, to examine the validity and application of these theories, the case study methodology is applied in order to combine practical deployment experiences. The analysis of these three companies is based on the impacts after the implementation of RFID. The findings from three case studies are summarized in this paper. RFID technology provides the improvement of supply chain efficiency, the reasonable management of warehouses and distributions, and the reduction of inventory costs and labour costs. It grants opportunities of the reduction of theft and counterfeiting. More accurate and instant information can be generated from this technology. However, two main limitations are discovered which are related to the cost and the privacy. These two problems affect the adoption of RFID and enable a number of suppliers to hesitate to apply this technology. Therefore, a further innovation of regulations and rules for RFID need to be issued and the advancement of RFID tags need to be explored for further research. Moreover, the cooperation among supply chain partners is another notably factor to widely apply RFID in the future.